Mirror-image-based disjoint multi-paths routing algorithm for maximizing communication efficiency - Duzhong Zhang; Quan Liu; Lin Chen; Wenjun Xu; Kehao Wang (EURASIP Journal on Wireless Communications and Networking, 2017)
Abstract The growing demands of high-speed and stable next generation 5G cellular networks become the main stream in these years. In order to overcome a bottleneck of high-speed communication which is caused by limited spectrum resources, cognitive radio (CR) network has been proposed as a promising technology in 5G networks. However, in CR networks, primary user (PU) networks lead another novel NP-Hard routing problem on continuous data transmission, especially for some low-latency scenario. To settle this problem, a new mirror-image-based disjoint multi-path routing algorithm (MIDMRA) is presented in this paper. A mirror image algorithm is employed in MIDMRA to simplify the routing challenge of CR network’s multi-channel environment, and an Optimal Path Selection mechanism is equipped to evaluate relationship between CR nodes and PUs when paths are being selected. Through theoretical and simulation analyses, MIDMRA has better performances on continuous communication under PU interferences than other multi-path routing algorithms.